Cryptococcal Disease in Diverse Hosts - Meya, David B.; Williamson, Peter R. (The New England journal of medicine, 2024)
Cryptococcus accounts for up to 180,000 deaths annually and 68% of HIV-related meningitis cases. The authors discuss diagnostic, preventive, and therapeutic strategies and the pathophysiological role of inflammatory syndromes.